1977
DOI: 10.1093/ageing/6.1.58
|View full text |Cite
|
Sign up to set email alerts
|

Improving Cognitive Performance in Psychogeriatric Patients: The Influence of Physical Exercise

Abstract: Performance measurement in psychogeriatric patients does not provide full insight into their potential abilities (competence). By systematically varing environmental conditions, performance levels can be seen to vary with them. The experiment discussed here demonstrates the influence of movement therapy on the results of some psychological tests. The subjects were old people (average age 82 years) who at an advanced age were confronted with mental and physical handicaps of such a nature that they had to be adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
3

Year Published

1987
1987
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 0 publications
2
30
0
3
Order By: Relevance
“…2 Specific cognitive effects of exercise for PWD include increase in mental status, 5,18 improved word fluency, 19 and increased free-recall and recognition performance. 20 The types of exercise forms tested include mobility and endurance exercises, isotonic and isometric exercises, endurance-seated exercises, light aerobic exercises, and range of motion and resistance exercises. 2 A growing body of research supports the positive benefits of exercise on physical outcomes in PWD.…”
Section: Background Effects Of Exercise On Cognitive Physical and Bmentioning
confidence: 99%
“…2 Specific cognitive effects of exercise for PWD include increase in mental status, 5,18 improved word fluency, 19 and increased free-recall and recognition performance. 20 The types of exercise forms tested include mobility and endurance exercises, isotonic and isometric exercises, endurance-seated exercises, light aerobic exercises, and range of motion and resistance exercises. 2 A growing body of research supports the positive benefits of exercise on physical outcomes in PWD.…”
Section: Background Effects Of Exercise On Cognitive Physical and Bmentioning
confidence: 99%
“…Early experimental studies regarding the eVects of physical exercise on neuropsychological function in older persons (Diesfeldt and Diesfeldt-Groenendijk 1977;Molloy et al 1988) and recent meta-analyses of experimental studies (Colcombe and Kramer 2003;Heyn et al 2004) revealed, that physical activity not only increases strength, physical Wtness and functional performance, but also results in improvements in cognitive functions. Various Wndings of neurophysiological research suggest that mental and physical activities enhance synaptic connections between the brain cells and neuronal plasticity (Bennett et al 1996;Spatz 1996), i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Nonaerobic group training interventions, including stretching, balance and coordination activities performed in a game context have been shown to improve working memory in a group of nursing home residents with various diagnoses [40] and in AD [41]. Additionally, yoga has been found to improve selective attention in middle- in animals were identified.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…In humans, aerobic exercise was shown to be more effective than non-aerobic exercise in all studies comparing the two, but some studies on elderly individuals with AD demonstrated that non-aerobic exercise (i.e., movement therapy) may have more of an effect on cognition than no exercise [40,41]. Obviously, studies using healthy adults were more likely of higher intensity exercise and studies involving the elderly and/or neurologicallydisabled patients were more likely to use lowerintensity or non-aerobic exercise.…”
Section: Translational Neurosciencementioning
confidence: 99%